Perancangan UI/UX pada Website Aerialmovie Menggunakan Metode Design Thinking - Mannuel Valent Krisnandyo; T. Arie Setiawan Prasida; Peni Pratiwi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
In expanding the market reach of Aerialmovie services through information dissemination, several issues were identified with the promotional media used, resulting in the current scope of information only reaching certain clients. This study discusses the design of a website-based UI/UX as a medium for disseminating information and promotional tools for Aerialmovie. The UI/UX design on the website uses the design thinking method to identify existing problems. Qualitative and quantitative approaches are used as means of data collection. The UI/UX design is evaluated using the usability testing method, and the results show that the application of design thinking improves the UI/UX design of the Aerialmovie website because it helps to understand the target users, so that they feel more comfortable and find it easier to access the Aerialmovie website.